Ferromagnetic powder composition and method for producing the same

JP2026536506APending Publication Date: 2026-10-30HOGANAS AB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2026521503
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-30
Filing Date
2024-10-25
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

【0020】 上記に言及された目的の少なくとも1つ、又は以下の説明から明らかとなるさらなる目的の少なくとも1つは、本明細書で提案される技術の第2の態様によれば、 強磁性粉末組成物であって、 ·本明細書で提案される技術の第1の態様による強磁性粉末組成物と、 ·さらなる強磁性粉末組成物と、 を含み、 前記さらなる強磁性粉末組成物は、前記強磁性粉末組成物の軟磁性鉄系コア粒子とは異なる軟磁性鉄系コア粒子を含み、 好ましくは、前記さらなる強磁性粉末組成物の軟磁性鉄系コア粒子は、前記強磁性粉末組成物の軟磁性鉄系コア粒子よりも高い電気抵抗率及び/又は硬度を有する鉄合金を含むか、又はそれからなる、強磁性粉末組成物。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026536506000001_ABST
    Figure 2026536506000001_ABST
Patent Text Reader

Abstract

A ferromagnetic powder composition comprising (i) soft magnetic iron-based core particles and (ii) a first coating that at least partially covers and is in direct contact with the surface of the core particles, wherein the first coating is a. a silicate of the general formula (K2O)α(SiO2)β, where α is the number of moles of K2O and β is the number of moles of SiO2, and the β / α molar ratio is in the range of 0.5 to 4.1, and the silicate is present in an amount of 0.02% to 1.0% by weight calculated based on the total weight of the ferromagnetic powder composition, and b. optionally, D measured according to ISO (International Organization for Standardization) 13320-1 50 A ferromagnetic powder composition comprising c. particles of a compound containing bismuth and oxygen, having a size in the range of 0.1 μm to 10 μm, and a dopant dissolved as an oxoanion or hydroxyanion in silicate (a). A second coating may be provided. A method for producing the composition, an object containing the composition, and a method for producing the object.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] Technical field The technologies proposed herein generally relate to the field of ferromagnetic powder compositions containing soft magnetic iron core particles and methods for producing ferromagnetic powder compositions. [Background technology]

[0002] background Ferromagnetic powders include soft magnetic composite (SMC) powders containing soft magnetic core particles (usually iron-based) with an electrically insulating coating on each particle. Such powders can be used to obtain soft magnetic components or members by compressing the powder into a desired shape, for example. These components or members, also known as soft magnetic composites, can be used in a wide range of applications as a substitute for laminated steel components in electric motors, generators, and electromagnets.

[0003] Two important properties of soft magnetic core particles and corresponding components made from such particles are permeability μ and core loss characteristics P. c The permeability μ of a material is an indicator of its ability to be magnetized or to carry magnetic flux. Maximum permeability (μ) max ) is defined as the maximum value of B / H, i.e., the ratio of magnetizing force B or magnetic field strength to induced magnetic flux H. When magnetic materials are exposed to a fluctuating magnetic field, energy loss occurs due to both hysteresis loss and eddy current loss. Hysteresis loss (DC loss), which constitutes the majority of total core loss in most motor applications, is caused by the consumption of energy required to overcome the coercive magnetic force within a component made from soft magnetic core particles, resulting in residual magnetism, or residual magnetic field B. R , and coercivity H C It is affected by.

[0004] The magnetic force retained within the component can be minimized by enhancing the quality and purity of the soft magnetic core particles, and in particular by subjecting the component to a heat treatment that triggers the release of stresses caused by compressive shear forces within the component. Energy loss is further caused by eddy current loss (AC loss) induced by the induction of electric current in the member due to varying magnetic flux caused by alternating current (AC) conditions. Eddy current loss is minimized by an electrically insulating coating on each particle, which thereby insulates the soft magnetic core particles from one another. Therefore, the resistivity R of the coating becomes a critical parameter for defining the properties and usability of the soft magnetic core particles. The level of electrical resistivity R required to minimize the AC loss of a member made from soft magnetic core particles depends on the size distribution of the soft magnetic core particles, the size of the member or the cross-sectional area of the magnetic flux, and the frequency of the alternating magnetic field in which the member is used.

[0005] European Patent No. 2252419 generally discloses a ferromagnetic powder composition comprising soft magnetic iron-based core particles, wherein the surface of the core particles is provided with a first inorganic insulating layer and at least one metal-organic layer located outside the first layer.

[0006] U.S. Patent No. 10,741,316 generally discloses a ferromagnetic powder composition comprising soft magnetic iron-based core particles, wherein the surface of the core particles is coated with at least one phosphorus-based inorganic insulating layer, and then at least partially covered with one or more metal-organic compounds.

[0007] European Patent No. 3411169 generally discloses a powder mixture comprising phosphorus-coated iron alloy particles and phosphorus-coated iron particles.

[0008] International Publication No. 2020 / 252551 generally relates to a particulate material comprising ferromagnetic particles covered by at least one oxide layer composed of nanoparticles and at least one vitreous layer covering the oxide layer.

[0009] BE44486 generally relates to a method for constructing a magnetic core by mixing particles of a magnetic material covered with an insulator with a particle separation material.

[0010] Despite the advantages provided by the techniques described in the literature cited above, there remains a need to provide further ferromagnetic powder compositions containing soft magnetic core particles with improved electrical, magnetic, and / or structural properties.

[0011] More specifically, there remains a need to enable heat treatment at higher temperatures while maintaining an acceptable electrical resistivity of the electrical insulating coating on each particle. Meeting this need will, among other things, provide improved aging properties due to the improved coverage of the coating, as well as higher resistivity for a given coercivity level and coating density / thickness level. Furthermore, this will also provide improvements to the properties of harder particles that undergo less plastic deformation during compression and therefore require higher relaxation temperatures during heat treatment. [Overview of the Initiative] [Problems that the invention aims to solve]

[0012] the purpose The first and second objects of the techniques proposed herein relate to providing ferromagnetic powder compositions and mixtures comprising soft magnetic core particles having improved electrical, magnetic, and / or structural properties.

[0013] A further object of the technology proposed herein is to provide ferromagnetic powder compositions and mixtures comprising soft magnetic core particles that provide an improved balance between two or more of the electrical, magnetic, and / or structural properties.

[0014] A further objective of the techniques proposed herein is to provide ferromagnetic powder compositions and mixtures having improved aging characteristics and higher resistivity for a given coercivity level and coating density / thickness level.

[0015] A further object of the techniques proposed herein is to provide ferromagnetic powder compositions and mixtures that can be used to manufacture objects having improved thermal aging properties.

[0016] A third object of the technology proposed herein relates to providing a method for producing ferromagnetic powder compositions and mixtures.

[0017] A fourth object of the technology proposed herein relates to providing a method for producing an object from a ferromagnetic powder composition or mixture.

[0018] The fifth and sixth objects of the technology proposed herein relate to objects comprising a compressed ferromagnetic powder composition or mixture, and objects manufactured from a ferromagnetic powder composition or mixture. [Means for solving the problem]

[0019] overview At least one of the purposes mentioned above, or at least one of the further purposes that become apparent from the following description, is possible according to the corresponding first and third embodiments of the technology proposed herein. A ferromagnetic powder composition, (i) Soft magnetic iron core particles, (ii) A first coating that at least partially covers the surface of the core particle and is in direct contact with the surface of the core particle, Includes, The first coating described above is a. A silicate with the general formula (K2O)α(SiO2)β, where α is the number of moles of K2O, β is the number of moles of SiO2, and the molar ratio of β / α is in the range of 0.5 to 4.1. i. The silicate is present in an amount of 0.02% to 1.0% by weight, calculated based on the total weight of the ferromagnetic powder composition, and b. Optionally, D measured according to ISO (International Organization for Standardization) 13320-1 50 Particles of a compound containing bismuth and oxygen, which are in the range of 0.1 μm to 10 μm, c. A dopant dissolved as an oxoanion or hydroxyanion in the silicate (a), A ferromagnetic powder composition containing, and a method for producing a ferromagnetic powder composition, (i) The step of providing soft magnetic iron-based core particles, (ii) The step of bringing soft magnetic iron core particles into contact with a first aqueous solution, Includes, The first aqueous solution is a. A silicate with the general formula (K2O)α(SiO2)β, where α is the number of moles of K2O, β is the number of moles of SiO2, and the molar ratio of β / α is in the range of 0.5 to 4.1. i. The silicate is present in an amount of 0.02% to 1.0% by weight, calculated based on the total weight of the ferromagnetic powder composition. b. Optionally, D measured according to ISO 13320-1 50 Particles of a compound containing bismuth and oxygen, which are in the range of 0.1 μm to 10 μm, c. A dopant dissolved as an oxoanion or hydroxyanion in the silicate (a), d. Optionally, D measured according to ISO 13320-1 50 Nanoparticles with a size of 10 nm to 200 nm, or alternatively, 6 to 120 nm as determined according to ISO 9277:2022. 2 Nanoparticles having a specific surface area (SSA) of / g, A method that includes this.

[0020] At least one of the purposes mentioned above, or at least one further purpose that becomes apparent from the following description, is, according to a second aspect of the technology proposed herein. A ferromagnetic powder composition, • A ferromagnetic powder composition according to a first aspect of the technology proposed herein, • Further ferromagnetic powder compositions, Includes, The further ferromagnetic powder composition comprises soft magnetic iron core particles that are different from the soft magnetic iron core particles of the ferromagnetic powder composition. Preferably, the ferromagnetic powder composition comprises, or consists of, an iron alloy having higher electrical resistivity and / or hardness than the soft magnetic iron core particles of the ferromagnetic powder composition.

[0021] At least one of the purposes mentioned above, or at least one further purpose that becomes apparent from the following description, is possible according to a fourth aspect of the technology proposed herein. A method for manufacturing an object, The method described herein is a method for producing an object from a ferromagnetic powder composition according to a first aspect of the technology proposed herein or a ferromagnetic powder mixture according to a second aspect of the technology proposed herein. (i) A step of obtaining a compressed member by compressing a ferromagnetic powder composition according to a first aspect of the technology proposed herein or a ferromagnetic powder mixture according to a second aspect of the technology proposed herein in a die at a compression pressure in the range of 300 to 2000 MPa, preferably 400 to 1200 MPa, (ii) The step of obtaining the object by heat-treating the compression member in a non-reducing atmosphere, preferably in an atmosphere containing 0 to 22% by weight, more preferably 0.5 to 2% by weight of oxygen (O2), at a temperature in the range of 300 to 800°C, preferably 400 to 750°C, more preferably 600 to 700°C, A method that includes this.

[0022] At least one of the purposes mentioned above, or at least one of the further purposes that become apparent from the following description, is possible according to the corresponding fifth and sixth aspects of the technology proposed herein. It is an object, An object comprising a compressed ferromagnetic powder composition according to the first aspect of the technology proposed herein or a compressed ferromagnetic powder mixture according to the second aspect of the technology proposed herein, and an object obtainable by the method according to the fourth aspect of the technology proposed herein, is achieved by. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] [Figure 1] Figure 1 shows a schematic cross-sectional view of a single particle of a ferromagnetic powder composition according to an embodiment of the first aspect of the technology proposed herein, illustrating soft magnetic iron-based core particles comprising a first coating that includes a silicate, nanoparticles, particles of a compound containing bismuth and oxygen, and a dopant, as well as a second coating that includes at least one metal-organic compound. DETAILED DESCRIPTION OF EMBODIMENTS FOR CARRYING OUT THE INVENTION

[0024] Detailed Description The corresponding first and third aspects of the technology proposed herein relate to a ferromagnetic powder composition, (i) soft magnetic iron-based core particles, and (ii) a first coating that at least partially covers the surface of the core particles and is in direct contact with the surface of the core particles, wherein the ferromagnetic powder composition comprises the first coating comprises a. a silicate of the general formula (K2O)α(SiO2)β, wherein α is the number of moles of K2O, β is the number of moles of SiO2, and the molar ratio β / α is in the range of 0.5 to 4.1, the silicate comprising i. the silicate is present in an amount of 0.02 wt% to 1.0 wt%, calculated based on the total weight of the ferromagnetic powder composition, b. optionally, particles of a compound containing bismuth and oxygen, having a D measured according to ISO 13320-1 50 in the range of 0.1 μm to 10 μm, c. A dopant dissolved as an oxoanion or hydroxyanion in the silicate (a), Regarding ferromagnetic powder compositions, and A method for producing a ferromagnetic powder composition, (i) The step of providing soft magnetic iron-based core particles, (ii) The step of bringing soft magnetic iron core particles into contact with the first aqueous solution, Includes, The first aqueous solution is a. A silicate of the general formula (K2O)α(SiO2)β, where α is the number of moles of K2O, β is the number of moles of SiO2, and the molar ratio of β / α is in the range of 0.5 to 4.1. ii. The silicate is present in an amount of 0.02% to 1.0% by weight, calculated based on the total weight of the ferromagnetic powder composition, b. Optionally, D measured according to ISO 13320-1 50 Particles of a compound containing bismuth and oxygen, which are in the range of 0.1 μm to 10 μm, c. A dopant dissolved as an oxoanion or hydroxyanion in the silicate (a), d. Optionally, D measured according to ISO 13320-1 50 Nanoparticles with a diameter of 10-200 nm, or alternatively, 6-120 nm as determined according to ISO 9277:2022. 2 Nanoparticles having a specific surface area (SSA) of / g, Regarding methods including

[0025] Accordingly, the techniques proposed herein are based on the inventors' recognition that the magnetic and electrical properties of ferromagnetic powder compositions, and components made from ferromagnetic powder compositions, can be further improved by dopants in a first coating on soft magnetic iron core particles. As can be seen from the examples and figures, the inclusion of dopants in the first coating provides components made from ferromagnetic powder compositions with improved aging characteristics and higher resistivity for a given coercivity level and coating density / thickness level. Specifically, these components can be heat-treated at higher temperatures while simultaneously maintaining acceptable electrical resistivity characteristics. In other words, the inclusion of dopants in the first coating provides better thermal stability and / or specific electrical resistivity for a given coercivity level and coating density / thickness level to the glassy coating formed from the first coating, and to any second coating applied thereon, when the ferromagnetic powder composition is compressed into a component and heat-treated. This enables heat treatment at higher temperatures. Heat treatment at higher temperatures allows for a more complete or complete release of the stress induced within the component when it is manufactured from a ferromagnetic powder composition, thus enabling the component to obtain a lower coercivity.

[0026] The improved thermal stability can be seen, alternatively, as obtaining or maintaining improved coverage of the glassy coating formed from the first coating and any second coating thereon, and therefore as obtaining or maintaining a higher electrical resistivity of the soft magnetic iron core particles, and consequently, a lower coercivity.

[0027] An additional advantage observed from components manufactured from ferromagnetic powder compositions is improved aging properties. Therefore, components manufactured from ferromagnetic powder compositions experience less degradation of properties, particularly resistivity and core loss, when subjected to the surrounding environment, such as elevated temperatures (e.g., 30-250°C), or corrosive gases or fluids, over time.

[0028] In a ferromagnetic powder composition, the silicate, particles of a compound containing bismuth and oxygen (if present), and the dopant are all provided in the same first coating. In other words, the particles of the compound containing bismuth and oxygen (if present) are dispersed in the silicate. The dopant is dissolved in the silicate.

[0029] Therefore, the dopant is distributed as an oxoanion or hydroxyanion in silicate (a). In other words, the oxoanion or hydroxyanion of the dopant is provided in silicate (a) so as to be distributed, for example. In yet another expression, the first coating contains the dopant as an oxoanion or hydroxyanion distributed in the silicate. The dopant dissolves in the silicate regardless of the state of the coating. This is because the oxoanion or hydroxyanion interacts with the silicate both in the first aqueous solution and in the first coating.

[0030] When a component manufactured from a ferromagnetic powder composition is heat-treated, a first coating, and any second coating applied thereon, then react to form a glassy coating consisting of silicates and dopants, in which particles of a compound containing bismuth and oxygen (if present) are dispersed.

[0031] The ferromagnetic powder composition contains a plurality of soft magnetic iron-based core particles. The soft magnetic iron-based core particles contain or consist of iron, or an iron alloy containing at least 90% iron, preferably at least 99% iron, more preferably at least 99.5% iron. The iron alloy may be an Fe-Si alloy iron containing up to 7% by weight, preferably up to 3% by weight of silicon, or other iron alloys selected from the group Fe-Al, Fe-Si-Al, Fe-Ni, Fe-Co, Fe-Ni-Co, or combinations or mixtures thereof of these alloys. The soft magnetic iron-based core particles may also contain a mixture of particles, such as a mixture of iron particles and iron alloy particles, or a mixture of particles made from two or more iron alloys. Preferably, the soft magnetic iron-based core particles are made from essentially pure iron, i.e., iron with unavoidable impurities. Preferably, at least 80% by weight, more preferably at least 90% by weight of all core particles have a diameter in the range of 20 to 1000 μm as measured according to ISO 4497.

[0032] Within this range, a more specific range may be more appropriate depending on the intended application of the component, part, or object manufactured from the ferromagnetic powder composition. Therefore, for high-frequency applications such as sensors, inductors, and converters, based on the total weight of the core particles, preferably at least 80% by weight, more preferably at least 90% by weight, for example at least 99% by weight of core particles, measured according to ISO 4497, with a diameter of 20-75 μm (approximately 50-55 μm). 50For low-to-medium frequency applications such as electric motors, generators, and converters, based on the total weight of the core particles, preferably at least 80% by weight, more preferably at least 90% by weight, for example at least 99% by weight, the core particles are measured according to ISO 4497 ​​in the range of 45-150 μm (100 mesh, corresponding to D50 of approximately 95-100 μm). For low-frequency applications such as electric motors, based on the total weight of the core particles, preferably at least 80% by weight, more preferably at least 90% by weight, for example at least 99% by weight, the core particles are measured according to ISO 4497 ​​in the range of 75-380 μm (40 mesh, corresponding to D50 of approximately 180-210 μm).

[0033] The soft magnetic iron core particles may be spherical or irregular in shape, with irregularly shaped particles being preferred. The apparent density (AD) is 2.8 to 4.0 g / cm³. 3 Preferably between 3.1 and 3.7 g / cm³ 3 It could be between these two points.

[0034] The soft magnetic iron core particles may be water-atomized iron powder, gas-atomized iron powder, or sponge iron powder. Generally, water-atomized soft magnetic iron core particles have an irregular shape.

[0035] The first coating at least partially covers and is in direct contact with the surface of the core particles. Preferably, the first coating covers all of at least 50% by weight of the surface of the core particles in the ferromagnetic powder composition, for example, all of at least 75% by weight of the surface. More preferably, the first coating covers all of at least 90% by weight of the surface of the core particles in the ferromagnetic powder composition, for example, all of at least 95% by weight, for example, all of at least 99% by weight of the surface.

[0036] In other words, the first coating preferably covers at least 50%, for example at least 75%, more preferably at least 90%, for example at least 95%, or for example at least 99% of the total surface area of ​​the core particles.

[0037] Typically, the first coating, and the second coating (if present), have an average thickness in the range of 20 to 100 nm. The combined total thickness of the first and second coatings is usually about 20 to 200 nm, with a permeability of about 400 to 600. The coating thickness can be estimated from the permeability; for a 40-mesh core particle, a maximum relative permeability of about 3000 corresponds to a thickness of zero, and a maximum relative permeability of about 700 corresponds to a thickness of about 20 nm.

[0038] General formula (K2O)α(SiO2) β The silicate is potassium silicate, or alternatively, K-silicate, K-water glass, potassium water glass, or simply silicate as used herein.

[0039] The β / α molar ratio (i.e., the molar ratio of SiO2 to K2O) is between 0.5 and 4.1. Preferably, the β / α molar ratio is between 2.0 and 3.75, and more preferably, the β / α molar ratio is between 2.5 and 3.5.

[0040] Therefore, the molar ratio β / α can alternatively be in the range of 2.0 to 4.1.

[0041] The silicate is present in an amount of 0.02 to 1.0% by weight, more preferably 0.05 to 0.5% by weight, calculated based on the total weight of the ferromagnetic powder composition. Preferably, the silicate is present in an amount of 0.05 to 0.2% by weight, calculated based on the total weight of the ferromagnetic powder composition, when at least 80% by weight of the core particles are 75 μm or larger, and in an amount of 0.1 to 0.5% by weight, calculated based on the total weight of the ferromagnetic powder composition, when at least 80% by weight of the core particles are less than 75 μm. The first coating may be applied using an aqueous solution as shown, and it has been found that when soft magnetic iron core particles are brought into contact with such a solution, substantially all silicate and other components, such as particles (if present) and nanoparticles (if present) of compounds containing bismuth and oxygen, ultimately become part of the first coating. Thus, the content and ratio of components and soft magnetic iron core particles in the aqueous solution are carried over to the content and ratio of components and soft magnetic iron core particles in the first coating.

[0042] While particles of bismuth and oxygen-containing compounds are optional, it is preferable that they be included in the first coating to further improve the properties of the glassy coating formed from the silicate and dopant during heat treatment. If present, the particles of bismuth and oxygen-containing compounds are dispersed in the first coating, for example, in the silicate. During and after heat treatment, the particles of bismuth and oxygen-containing compounds react with the silicate and become incorporated into the formed glassy coating.

[0043] Particles of a compound containing bismuth and oxygen preferably contain bismuth oxides and hydroxides. Particles of a compound containing bismuth and oxygen preferably contain bismuth oxides and hydroxides. Preferably, D measured according to ISO 13320-1 50 The size is between 0.5 and 2 μm.

[0044] Preferably, the content of bismuth and oxygen-containing compound particles in the first coating is 0.025 to 0.3% by weight, preferably 0.05 to 0.25% by weight, more preferably 0.07 to 0.22% by weight, for example 0.08 to 0.22% by weight, for example 0.08 to 0.11% by weight, based on the total weight of the ferromagnetic powder composition. Example 8 shows that these ranges of bismuth and oxygen-containing compound particle content yield good results.

[0045] A content of 0.08–0.11% by weight is currently the best range for soft magnetic iron core particles with a size of 100 mesh.

[0046] When the soft magnetic iron core particles are larger, for example, 40 mesh size, the content of bismuth-containing compound particles is preferably at least 0.05% by weight, for example, 0.05 to 0.10% by weight.

[0047] When the soft magnetic iron core particles are smaller, for example, 200 mesh in size, the content of bismuth-containing compound particles is preferably at least 0.15% by weight, for example, 0.15 to 0.30% by weight.

[0048] The compound containing bismuth and oxygen can be selected from the group consisting of bismuth(III) oxide (Bi2O3) and bismuth(III) hydroxide (Bi(OH)3), and the compound containing bismuth and oxygen is preferably Bi(OH)3. As shown in Example 9, the presence of Bi2O3 or Bi(OH)3 particles increases the resistivity. Also, as shown in Example 9, the resistivity increases more with Bi(OH)3 particles than with Bi2O3 particles.

[0049] D measured according to ISO 13320-1 50 In ISO 13320-1, this is defined as the median particle size used on a volume basis, meaning that 50% of the particle volume is smaller than this diameter and 50% is larger.

[0050] In general, references to ISO standards in this specification are equivalent to references to SS (Swedish Standard)-ISO standards, where SS simply indicates that the ISO standard in question is adopted as a Swedish standard.

[0051] D measured according to ISO 13320-1 50 This can be determined, for example, using a Mastersizer 3000 from Malvern Instruments.

[0052] The dopant is dissolved in silicate (a) as an oxoanion or hydroxyanion. The oxoanion or hydroxyanion may be a monoanion or a polyanion, preferably a monoanion to maximize distribution in the silicate. In addition to the improved distribution, the use of a monoanion may also reduce the risk of increased melting temperature during heat treatment of the glassy coating formed from the first coating and any second coating applied thereon. Specifically, the increased melting temperature is thought to be caused by the presence of longer polyanions competing with polysilicate ions in the glassy coating. Such an increased melting temperature may make it more difficult to obtain a good distribution in the glassy coating.

[0053] The dissolution of a dopant as an oxoanion or hydroxyanion includes the fact that the dopant is an oxoanion or hydroxyanion dopant. The term “dopant” includes both compounds that form an oxoanion or hydroxyanion when dissolved in a silicate or an aqueous solution of a silicate, as well as the oxoanion or hydroxyanion itself. Since the first aqueous solution containing a silicate is usually alkaline, the dopant may be a compound that forms an oxoanion or hydroxyanion when dissolved in an alkaline aqueous solution.

[0054] Generally, the dopant content can be 0.5 to 30 mol%, preferably 1 to 30 mol%, and more preferably 1 to 25 mol%, based on the molar content of K (potassium) in the first coating.

[0055] Contact between the soft magnetic iron core particles and the first aqueous solution can be carried out, for example, by mixing in a mixer. As a result of contact between the soft magnetic iron core particles and the first aqueous solution, a first coating is formed on the magnetic iron core particles so as to at least partially cover them. In other words, a method according to a third aspect of the art proposed herein produces soft magnetic iron core particles coated with the first coating, i.e., a ferromagnetic powder composition according to the first aspect of the art proposed herein. Soft magnetic iron core particles coated with the first coating and optionally also coated with the second coating described below may be alternatively referred to as coated core particles or coated soft magnetic iron core particles.

[0056] Preferably, the first coating is further D measured according to ISO 13320-1. 50 Nanoparticles with a size of 10-200 nm, or alternatively, nanoparticles with a specific surface area (SSA) of 6-120 m² as measured according to ISO 9277:2022. 2 Contains nanoparticles at / g.

[0057] As seen in the examples, particularly Example 1, the inclusion of nanoparticles further improves the electrical resistivity of the glassy coating formed from the first coating and any second coating applied thereon. The inclusion of nanoparticles works even better with dopants.

[0058] Nanoparticles (if present) are dispersed in the first coating, for example, in a silicate. During and after heat treatment, the nanoparticles are embedded in the formed glassy coating.

[0059] The nanoparticles were measured according to ISO 13320-1. 50The range is 10-200 nm.

[0060] D measured according to ISO 13320-1 50 In ISO 13320-1, this is defined as the median particle size used on a volume basis, meaning that 50% of the particle volume is smaller than this diameter and 50% is larger.

[0061] In general, references to ISO standards in this specification are equivalent to references to SS-ISO standards, where SS simply indicates that the ISO standard in question is adopted as a Swedish standard.

[0062] D measured according to ISO 13320-1 50 This can be determined, for example, using a Mastersizer 3000 from Malvern Instruments.

[0063] An alternative parameter for determining the size of nanoparticles is the specific surface area (SSA) [m²]. 2 [ / g] is the surface area of ​​a particle per gram of particle.

[0064] Therefore, D in the range of 10-200 nm, measured according to ISO 13320-1, is 50 6-120m 2 It can be equivalently replaced by the specific surface area (SSA) within the range of / g.

[0065] The surface area aggregation (SSA) of nanoparticles is preferably measured using the Brunauer-Emmett-Teller (BET) method, which is a method for determining the specific surface area of ​​a solid by gas adsorption.

[0066] More preferably, the SSA of the nanoparticles is measured according to ISO 9277:2022.

[0067] Therefore, D in the range of 10-200 nm, measured according to ISO 13320-1, is 50 This is determined according to ISO 9277:2022, ranging from 6 to 120m. 2It can be equivalently replaced by the specific surface area (SSA) of / g.

[0068] Preferably, the specific surface area (SSA) of the nanoparticles is 10 to 50, more preferably 10 to 30, and most preferably 15 to 20 m². 2 / g is one example: 18m 2 The values ​​are per gram. As mentioned above, these ranges are preferably measured according to ISO 9277:2022.

[0069] The specific surface area can be measured using the Micromeritics TriStar 3000 gas adsorption device, which calculates the BET surface area.

[0070] For comparison, assuming the particles are spherical, the average diameter of nanoparticles can be calculated from the specific surface area. The formula for calculating the average particle diameter (nanometers) is 6000 / (BET surface area (m²) 2 / g))×(density(g / cm 3 )) is Y2O3 (density 5.01 g / cm³). 3 ) In the case of 120, 6, 50, 10, and 18m 2 The specific surface areas per g result in average diameters of 10,200, 24, 120, and 67 nm, respectively.

[0071] Preferably, the nanoparticles are measured according to ISO 13320-1. 50 The nanoparticles are 10-100 nm in size. Most preferably, the nanoparticles are measured according to ISO 13320-1. 50 The range is 20-100 nm.

[0072] The distance between the former is 12-120m 2 Corresponds to / g SSA, with the latter interval being 12-60m 2 This corresponds to the SSA for / g.

[0073] D measured according to ISO 13320-1 50 The ratio is preferably 10 to 100, and 90% by weight of the particles shall have a maximum diameter of 1 to 500 nm.

[0074] In the examples, nanoparticles are generally D 50 The size is 10 nm, and it has been shown that nanoparticles of this size provide the best results.

[0075] Alternatively, the nanoparticles may have a diameter of 1 to 200 nm, preferably 1 to 50 nm, more preferably 5 to 50 nm, for example 30 to 50 nm or for example 5 to 20 nm, for example 10 nm.

[0076] When carrying out a method according to a third aspect of the technology proposed herein, the nanoparticles provided or obtained are aggregated into agglomerates having a diameter greater than 200 nm, and / or the aggregated nanoparticles have a diameter greater than 200 nm. 50 It is possible that these aggregates may have nanoparticles that are well distributed within the first coating, and therefore, as described above, a desired D of 1 to 200 nm or less is preferred. 50 Alternatively, the nanoparticles should be completely or partially crushed to obtain nanoparticles with a certain diameter or to increase the number of particles, because uniformly dispersed nanoparticles in the first coating are preferable. If the nanoparticles used in this method contain a significant amount of aggregates and no further crushing is performed on the nanoparticles, the molar percentage of nanoparticles in the first coating will contain no aggregates or only small amounts of aggregates, resulting in a lower D 50 Alternatively, the amount may be preferably increased compared to when nanoparticles with a diameter are used.

[0077] Crushing preferably occurs before or during the preparation of the first aqueous solution, or during contact between the soft magnetic iron core particles and the first aqueous solution. As an example, ultrasonic treatment may be used for crushing.

[0078] The nanoparticles are preferably selected from the group consisting of Y2O3 nanoparticles, ZrO2 nanoparticles, ZnO nanoparticles, Mg(OH)2 nanoparticles, MgO nanoparticles, CaCO3 nanoparticles, Al2O3 nanoparticles, SiO2 nanoparticles, and TiO2 nanoparticles, and more preferably the nanoparticles include or consist of Y2O3 nanoparticles.

[0079] The nanoparticles may include a mixture of nanoparticles, for example, a mixture of two or more of the listed nanoparticles. However, currently, it is preferable that only one type of nanoparticle, for example, preferably Y2O3 nanoparticles, be present in the first coating.

[0080] The dopant is effective against a wide variety of nanoparticles.

[0081] As seen in Example 8, numerous different nanoparticles are effective in obtaining improved magnetic and electrical properties for objects manufactured from ferromagnetic powder compositions. Furthermore, Example 8 demonstrates that Y2O3 nanoparticles, also known as yttria nanoparticles and yttrium oxide nanoparticles, provide what are currently considered to be the best magnetic and electrical properties.

[0082] The content of nanoparticles in the first coating is preferably 1 to 30 mol%, more preferably 1 to 20 mol%, based on the molar content of K (potassium) in the first coating. These common molar content of nanoparticles provide good results, as seen, for example, in Example 8.

[0083] Preferably, the first coating is -Based on the K content of the first coating, 1 to 25 mol%, more preferably 8 to 22 mol%, most preferably 10 to 20 mol%, for example 20 mol%, of Y2O3 nanoparticles, or -Based on the K content in the first coating, 1 to 20 mol%, preferably 1 to 15 mol%, more preferably 1 to 10 mol%, for example 5 mol%, of ZrO2 nanoparticles, or - Based on the K content in the first coating, 1 to 20 mol%, preferably 5 to 20 mol%, more preferably 10 to 20 mol%, of Mg(OH)2 nanoparticles, or -Based on the K content in the first coating, 1 to 20 mol%, preferably 5 to 20 mol%, more preferably 10 to 20 mol%, of CaCO3 nanoparticles, or -Based on the K content in the first coating, 1 to 20 mol%, preferably 5 to 20 mol%, more preferably 10 to 20 mol%, of ZnO nanoparticles, or -Based on the K content in the first coating, 1 to 30 mol%, preferably 10 to 30 mol%, more preferably 15 to 25 mol%, for example 20 mol%, of MgO nanoparticles, -Based on the K content in the first coating, 1 to 30 mol%, preferably 10 to 30 mol%, more preferably 15 to 25 mol%, for example 20 mol%, of TiO2 nanoparticles, - Based on the K content in the first coating, 1 to 20 mol%, preferably 5 to 15 mol%, more preferably 10 mol%, of Al2O3 nanoparticles, or -Based on the K content in the first coating, 1 to 20 mol%, preferably 1 to 10 mol%, more preferably 5 mol%, of ZnO nanoparticles, Includes.

[0084] Example 8 demonstrates that these various nanoparticle contentes yield good results. As described above, different nanoparticles may be combined in the first coating depending on these ranges.

[0085] Preferably, the nanoparticles include or consist of Y2O3 nanoparticles, and the content of nanoparticles in the first coating is 10 to 20 mol% based on the molar content of K (potassium) in the first coating.

[0086] As seen in Example 8, Y2O3 nanoparticles provide what are currently considered to be the best magnetic and electrical properties.

[0087] For reference, if 20 mol% of Y2O3 particles are contained in a first coating containing 0.1 wt% potassium silicate with a β / α molar ratio of 3.4 on 5 kg of soft magnetic iron core particles, this corresponds to 0.94 g of Y2O3 particles, or 0.0188 wt% based on the weight of the ferromagnetic powder composition.

[0088] Preferably, the dopant contains at least one element from Group 5, for example V (vanadium) or Nb (niobium), or at least one element from Group 6, for example Cr (chromium), W (tungsten), or Mo (molybdenum), or Al (aluminum) or P (phosphorus).

[0089] Preferred elements in Group 5 include V (vanadium), Nb (niobium), and Ta (tantalum).

[0090] Preferred elements in Group 6 include chromium (Cr), molybdenum (Mo), and tungsten (W).

[0091] Exemplary dopants include V (vanadium), Nb (niobium), Ta (tantalum), Cr (chromium), Mo (molybdenum), W (tungsten), and P (phosphorus). For example, V (vanadium), Nb (niobium), Ta (tantalum), Cr (chromium), Mo (molybdenum), and W (tungsten). For example, V (vanadium), Nb (niobium), Cr (chromium), Mo (molybdenum), and W (tungsten).

[0092] Elements of Groups 5 and 6 are known to form oxoanions or hydroxoanions in alkaline aqueous solutions. Aluminum (Al) can dissolve as a hydroxyanion in strongly alkaline solutions and can therefore be used as a dopant. Phosphorus can also be used in the form of phosphate salts, such as KHPO4, H3PO4, and (NH4)3PO4. Nb and tantalum, like W, Mo, and W, can form oxoanions and / or hydroxoanions.

[0093] Preferred dopants are those that dissolve readily in silicate solutions and are stable. Toxic dopants, such as ions containing Cr(VI), are less desirable.

[0094] The dopant is preferably provided to the first coating in contact with the soft magnetic iron core particles by dissolving a suitable compound containing the dopant, such as an oxide, in the first aqueous solution. This typically results in the provision of dopant ions in the first aqueous solution.

[0095] Preferred elements as dopants include Al, Nb, V, Mo, and Cr. More preferred elements include Al and Nb.

[0096] V (vanadium) is preferably provided to the first coating by dissolving vanadium pentoxide (V2O5) in a first aqueous solution in which the soft magnetic iron core particles are in contact. In a strongly alkaline aqueous solution, such as a potassium silicate solution, vanadium is mainly (VO4) 3- It forms ions (pH > 12). This is VO4 in the first aqueous solution. 3- This results in the provision of ions. In a less strongly alkaline environment, vanadium, similar to a polyphosphate chain, coordinates more than four oxo or hydroxo groups to form polyvanadate ions, such as (VO3). n - It tends to form [a specific type of ion]. Therefore, the size of the vanadate ion can vary depending on the potassium concentration and the pH of the silicate solution.

[0097] It is considered preferable that dopant ions are not present as polyanions in the silicate before heat treatment in order to maximize the atomic distribution of dopants in the final glassy coating, which theoretically can increase the specific electrical resistivity of the bismuth-silicate glass.

[0098] Mo (molybdenum) is preferably provided to the first coating by dissolving molybdenum(VI) oxide (MoO3) in a first aqueous solution in which the soft magnetic iron core particles are in contact. This is similar to tungstate ions, but with molybdate ions (MoO4). 2- This results in the provision of a first aqueous solution.

[0099] W (tungsten) is preferably provided to the first coating by dissolving tungsten(VI) oxide (WO3) in a first aqueous solution in which the soft magnetic iron core particles are in contact. This is similar to vanadate ions, but with tungstate ions (WO4) 2- This results in the provision of a first aqueous solution.

[0100] Aluminum (Al) is preferably provided to the first coating by dissolving aluminum(III) hydroxide (Al(OH)3) in a first aqueous solution in which the soft magnetic iron core particles are in contact. - This results in the provision of ions.

[0101] Preferably, - The dopant contains V, and the dopant content in the first coating is 1 to 30 mol%, preferably 5 to 20 mol%, more preferably 5 to 15 mol%, based on the molar content of K (potassium) in the first coating. - The dopant contains Nb, and the dopant content in the first coating is 1 to 30 mol%, preferably 5 to 20 mol%, and more preferably 5 to 15 mol%, based on the molar content of K in the first coating. - The dopant contains Cr, and the dopant content in the first coating is 1 to 30 mol%, preferably 5 to 20 mol%, more preferably 5 to 15 mol%, based on the molar content of K in the first coating. - The dopant contains Mo, and the dopant content in the first coating is 1 to 30 mol%, preferably 5 to 20 mol%, and more preferably 5 to 15 mol%, based on the molar content of K in the first coating. - The dopant contains W, and the dopant content in the first coating is 1 to 30 mol%, preferably 5 to 20 mol%, more preferably 5 to 15 mol%, based on the molar content of K in the first coating. - The dopant contains Al, and the dopant content in the first coating is 0.5 to 5 mol%, preferably 1 to 3 mol%, more preferably 1.71 to 2.58 mol%, and / or, based on the molar content of K in the first coating. - The dopant contains P, and the dopant content in the first coating is 1 to 30 mol%, preferably 5 to 20 mol%, and more preferably 5 to 15 mol%, based on the molar content of K in the first coating.

[0102] More preferably, the dopant contains V, and the dopant content in the first coating is 1 to 30 mol%, preferably 5 to 20 mol%, and more preferably 10 to 15 mol%, based on the molar content of K in the first coating.

[0103] As shown in Examples 1 and 3, 10–15 mol% of the V dopant results in higher electrical resistivity for a given coercivity level and coating density / thickness level. This is thought to be due to a better distribution of the glassy coating formed from the first coating and any second coating applied thereon during heat treatment.

[0104] Alternatively, the dopant may contain Al, and the dopant content in the first coating is 0.5 to 5 mol%, preferably 1 to 3 mol%, more preferably 1.5 to 2.7 mol%, for example 1.71 to 2.58 mol%, based on the molar content of potassium K in the first coating.

[0105] As seen in Example 7, providing the Al dopant to the first coating at this concentration range allows for higher heat treatment temperatures, resulting in lower coercivity while maintaining good electrical resistivity. Although the effect is smaller than in the case of V, Al has a smaller environmental impact and lower health risks.

[0106] Preferably, the ferromagnetic powder composition further comprises: (iii) A second coating that at least partially covers the surface of the core particles and / or the first coating, the second coating comprising: a. General formula R1[(R1) x (R2) y (M)] n O n-1 R1(I) or R2[M(OH)] 2(n+1) ] (n+1) O (n) R2(II) At least one metal-organic compound having, Here, M is selected from the group consisting of Si, Ti, Al, and Zr, O is oxygen, R1 is a hydrolyzable group, R2 is an organic moiety, at least one R2 contains at least one nitrogen-containing group, preferably an amino group, n is the number of repeating units which is an integer from 1 to 20, x is 0 or 1, y is 1 or 2, and x+y is 2. The content of at least one metal-organic compound is 0.05 to 0.40% by weight, preferably 0.1 to 0.30% by weight, based on the total weight of the ferromagnetic powder composition.

[0107] The second coating further improves the electrical, structural, and magnetic properties of components or members manufactured from ferromagnetic powder compositions. While not intended to be theoretically bound, the second coating may provide lubrication and additional silicon and carbon, thereby appearing to facilitate the formation of a glassy coating during heat treatment.

[0108] R1 may be an alkoxy group having fewer than 4, preferably fewer than 3, carbon atoms. R2 is an organic moiety, meaning that the R2 group contains an organic moiety or part. R2 preferably contains 1 to 6, more preferably 1 to 3, carbon atoms. R2 may further contain one or more heteroatoms selected from the group consisting of N, O, S, and P. The R2 group may be linear, branched, cyclic, or aromatic. R2 may contain one or more of the following functional groups: amine, diamine, amide, imide, epoxy, hydroxyl, ethylene oxide, ureid, urethane, isocyanate, acrylate, glyceryl acrylate, benzylamino, vinyl-benzylamino. The R2 group may vary between any of the above-described functional R2 groups and a hydrophobic alkyl group having repeatable units.

[0109] When n=1, the metal-organic compound is either a monomer (Formula I) or a dimer (Formula II). If the metal-organic compound is a monomer, it can be selected from the group consisting of trialksoxy and dialkoxysilanes, titanates, aluminates, or zirconates. Therefore, the monomers of the metal-organic compound can be selected from 3-aminopropyl-trimethoxysilane, 3-aminopropyl-triethoxysilane, 3-aminopropyl-methyl-diethoxysilane, N-aminoethyl-3-aminopropyl / ethyl / methyl-alkoxysilane, for example N-aminoethyl-3-aminopropyl-trimethoxysilane and N-aminoethyl-3-aminopropyl-methyl-dimethoxysilane, 1,7-bis(triethoxysilyl)-4-azaheptane, triaminofunctional propyl-trimethoxysilane, 3-ureidopropyl-triethoxysilane, 3-isocyanatopropyl-triethoxysilane, tris(3-trimethoxysilylpropyl)-isocyanurate, O-(propargyloxy)-N-(triethoxysilylpropyl)-urethane, 1-aminomethyl-triethoxysilane, 1-aminoethyl-methyl-dimethoxysilane, or mixtures thereof.

[0110] For n=2 to 20, the metal-organic compound is an oligomer. The metal-organic compound oligomer can be selected from alkoxy-terminated alkyl-alkoxy-oligomers of silane, titanate, aluminate, or zirconate. Therefore, the metal-organic compound oligomer can be selected from methoxy, ethoxy or acetoxy-terminated amino-silsesquioxane, amino-siloxane, oligomer 3-aminopropyl-methoxy-silane, 3-aminopropyl / propyl-alkoxy-silane, N-aminoethyl-3-aminopropyl-alkoxy-silane, or N-aminoethyl-3-aminopropyl / methyl-alkoxy-silane, or mixtures thereof.

[0111] Examples of suitable metal-organic compounds include, in particular, Dynasylan® 1146 and Dynasylan SIVO 203 from Evonik Industries AG, or XIAMETER® OFS-6020 Silane from Dow Chemical Company.

[0112] Aqueous amino or polyfunctional silane systems also consist of metal-organic compounds, such as the corresponding Dynasylan HYDROSIL products supplied by Evonik Industries AG. In these products, the hydrolyzable alkoxy group is almost completely replaced by a hydroxyl group, i.e., as shown in formula (II), but the functionality is similar, for example, a hydrophobic alkyl group combined with an amino or diaminoalkyl group. Examples include the Dynasylan HYDROSIL 2627, 2776, and 1151 silane systems. Examples of such compounds may be 1,3-bis(3-aminopropyl)disiloxane-1,1,3,3-tetrol or (3-aminopropyl)({[(propyl)dihydroxysilyl]oxy})silanediol.

[0113] Furthermore, D, which is optionally included in the first coating and measured according to ISO 13320-1 50It is further assumed that some or all of the particles of bismuth and oxygen-containing compounds having a size in the range of 0.1 to 10 μm may also be provided for the second coating or alternatively.

[0114] Example 8 demonstrates that various metal-organic compounds in the second coating can be successfully used in the ferromagnetic powder composition.

[0115] Preferably, at least one metal-organic compound has general formula (I).

[0116] Alternatively, at least one metal-organic compound has general formula (II).

[0117] The ferromagnetic powder composition preferably further comprises: (iv) A lubricant, preferably a particulate lubricant.

[0118] Incorporating a lubricant into a ferromagnetic powder composition improves compression and results in increased density and strength of the object produced from the ferromagnetic powder composition. The lubricant may be selected from the group consisting of primary and secondary fatty acid amides, trans-amides (bisamides), or fatty acid amides or alcohols. The lubricating portion of the lubricant may be a saturated or unsaturated chain containing 12 to 22 carbon atoms. The lubricant may preferably be selected from stearamide, behenyl alcohol, erucamide, stearyl erucamide, erucyl stearamide, erucyl alcohol, or ethylene-bis-stearamide (i.e., EBS (Ethylene Bis-Stearamide) wax or amide wax). Preferably, the lubricant is an amide wax. A mixture of stearamide or behenyl alcohol and an amide wax is also preferred. One example is 0.1% by weight of stearamide combined with 0.3% by weight of an amide wax.

[0119] The lubricant may be present in an amount of 0.05 to 0.80% by weight, preferably 0.20 to 0.40% by weight, of the ferromagnetic powder composition. When a very low amount of lubricant (0.05 to 0.20% by weight) is added to the composition, compression and demolding can be facilitated by using die wall lubrication (DWL). Low amounts of internal lubricant improve the compact density, permeability, and mechanical strength.

[0120] A second aspect of the technology proposed herein relates to a ferromagnetic powder composition comprising: -A ferromagnetic powder composition according to a first aspect of the technology proposed herein. - Further ferromagnetic powder compositions. The further ferromagnetic powder composition contains soft magnetic iron core particles that are different from the soft magnetic iron core particles of the ferromagnetic powder composition. Preferably, the soft magnetic iron core particles of the further ferromagnetic powder composition include or consist of an iron alloy having higher electrical resistivity and / or hardness than the soft magnetic iron core particles of the ferromagnetic powder composition.

[0121] This is advantageous in that it allows for further adjustment of the magnetic and electrical properties of components or members manufactured from ferromagnetic powder compositions. Preferably, if the soft magnetic iron core particles of the additional ferromagnetic powder composition contain or consist of an iron alloy having a higher electrical resistivity than the soft magnetic iron core particles of the ferromagnetic powder composition, the ferromagnetic powder mixture will have even lower core losses at high frequencies. The soft magnetic iron core particles of the additional ferromagnetic powder composition are usually also harder and may therefore provide further improvements in properties.

[0122] The soft magnetic iron core particles of the further ferromagnetic powder composition preferably include or consist of an iron alloy selected from the group consisting of FeSi, FeAl, FeSiAl, FeNi, FeCo, and FeNiCo, or a combination or mixture of such alloys. FeSi (usually 3 to 6.8 wt% Si) and FeSiAl (also known as Sendust; usually 9 wt% Si and 6 wt% Al, or 3.5 wt% Si and 3 wt% Al) are particularly preferred.

[0123] The content of the additional ferromagnetic powder composition may be up to 60% by weight, for example 30-60% by weight, based on the weight of the ferromagnetic powder mixture having the ferromagnetic powder composition according to the first aspect of the technology proposed herein, but is usually 10-50% by weight, for example 20-40% by weight, for example 20-30% by weight. Furthermore, in medium-frequency or low-frequency applications, the content of the additional ferromagnetic powder composition is preferably low or absent in order to avoid reducing density, magnetic induction, and permeability. In contrast, in high-frequency applications, the content of the additional ferromagnetic powder composition may instead be increased to 90% by weight.

[0124] In the powder mixture, the soft magnetic iron core particles of the ferromagnetic powder composition preferably contain or consist of essentially pure iron, i.e., iron with unavoidable impurities.

[0125] Preferably, the further ferromagnetic powder composition further comprises a coating or surface treatment on the soft magnetic iron core particles therein. The coating or surface treatment preferably comprises the first coating and optionally a second coating as described above. However, usually, when an iron alloy is included, the soft magnetic iron core particles of the further ferromagnetic powder composition may be coated or treated with another coating, for example, by treatment with phosphoric acid diluted in acetone.

[0126] The soft magnetic iron core particles or further ferromagnetic powder composition preferably have the same particle size as the soft magnetic iron core particles of the ferromagnetic powder composition according to the first embodiment of the technology proposed herein, as further described above.

[0127] A third aspect of the technique proposed herein is as follows: (iii) drying the coated soft magnetic iron core particles, and / or (iv) The step of bringing coated soft magnetic iron core particles into contact with at least one metal-organic compound as described above, and / or (v) Mixing the coated soft magnetic iron core particles with the lubricant as described above, This may further include one or more of the following steps.

[0128] Step (iii) is preferably performed after step (ii). Step (iii) may be performed by heating the soft magnetic iron core particles while stirring them.

[0129] Step (iv) is preferably performed after step (ii) or (iii) and before step (v).

[0130] Step (v) is preferably performed after steps (iii) and (iv).

[0131] A fourth aspect of the technology proposed herein is a method for producing an object from a ferromagnetic powder composition according to the first aspect of the technology proposed herein, or from a ferromagnetic powder mixture according to the second aspect of the technology proposed herein, (i) A step of obtaining a compressed member by compressing a ferromagnetic powder composition according to a first aspect of the technology proposed herein, or a ferromagnetic powder mixture according to a second aspect of the technology proposed herein, in a die at a compression pressure in the range of 300 to 2000 MPa, preferably 400 to 1200 MPa, (ii) A step of obtaining an object by heat-treating a compressed member in a non-reducing atmosphere preferably containing 0 to 22% by weight, more preferably 0.5 to 2% by weight of oxygen (O2), at a temperature in the range of 300 to 800°C, preferably 400 to 750°C, more preferably 600 to 700°C, Regarding methods including

[0132] The compression may be cold die compression, warm die compression, or high-speed compression, preferably controlled die temperature compression (50-120°C) using unheated powder. During compression, the coated soft magnetic iron core particles are pressed against each other, deformed, and adhere to one another to form a compressed member. During heat treatment, the particles of the bismuth and oxygen-containing compound, together with the nanoparticles and silicate in the first coating and the amino groups and / or alkyl groups of the metal-organic compound in the second coating, form a bismuth-silicate glass uniformly distributed on the surface of the soft magnetic iron core particles, which provides the desired electrical resistivity between the individual particles of the compressed and heat-treated ferromagnetic powder composition in the finished object. Furthermore, the heat treatment relieves the stress formed during compression.

[0133] The heat treatment process may be carried out in a vacuum, a non-reducing, inert, or weakly oxidizing atmosphere, for example, in an atmosphere where the oxygen content in nitrogen is 0.01–3 wt%. In one embodiment, an essentially pure nitrogen atmosphere is used as the non-reducing atmosphere. In one embodiment, 0–22 wt% oxygen, preferably 0.5–2 wt% oxygen, is added. Higher temperatures, above 680–700°C, may require lower oxygen levels, such as 500–3000 ppm (0.05–0.3 wt%). Generally, the oxygen level may be higher during initial heating, for example, during delubrication. Optionally, the heat treatment may be carried out in an inert atmosphere and then rapidly exposed to an oxidizing atmosphere, such as a 0.5–22 wt% oxygen / nitrogen mixture, or a vapor / nitrogen mixture, to build a surface crust with higher strength and / or corrosion resistance. In one embodiment, the temperature may be up to 800°C. Heat treating a compression member at a temperature in the range of 300-800°C means that the compression member is exposed to temperatures in the range of 300-800°C. This is usually done for a period of time sufficient to cause the compression member to heat up to a temperature in the range of 300-800°C, for example, 20-120 minutes.

[0134] Typically, the heat treatment is carried out in three stages: a delubrication stage at approximately 300-400°C while the compression member is heated toward the hardening stage; a hardening stage at approximately 350-450°C (first temperature and time), in which the first coating hardens, thereby forming an electrically insulating glassy coating (in which silicate and any present silane are polymerized to form silicate glass) from the first coating and, if present, from the second coating; and a relaxation stage at 600-700°C (second temperature and time), in which the glassy coating flows to cover the core particles and the stress from compression is released. The temperature range of 300-800°C given for step (ii) above corresponds to this final (second) temperature. The first and second time periods can typically be 0-60 minutes each, for example, 1-60 minutes.

[0135] The compression member is more preferably heat-treated at a temperature below the glass crystallization temperature of the first coating. This is because crystallization of silicate in the coating layer can reduce the resistivity and mechanical strength of the silicate and the first coating. Furthermore, crystallization of silicate in the first coating can cause cracks in the glassy coating formed by the first and second coatings during heat treatment.

[0136] The heat treatment may include a delubrication step, during which the temperature may be between 400 and 500°C, for example, 420 to 480°C or 430 to 470°C. The atmosphere during the delubrication step may be an inert atmosphere, for example, an N2(g.) atmosphere.

[0137] Preferably, step (ii) includes heat-treating the compression member at a (second) temperature of at least 650°C, more preferably at at least 670°C, to substantially or completely relieve the stress in the compression member. The temperature at which the greatest stress relief occurs in the compression member is called the maximum relaxation temperature.

[0138] Preferably, step (ii) includes heat-treating the compression member at a (second) temperature of 670 to 700°C, preferably 680 to 700°C.

[0139] For heat treatment at higher second temperatures, for example between 700°C and 750°C, or between 750°C and 800°C, it is preferable to use a thicker first coating, i.e., a higher weight percentage of silicate, for example 0.25 wt%, because such a thicker coating provides an acceptable residual electrical resistivity while potentially offering even better aging properties. This also applies to ferromagnetic powder mixtures containing harder particles or alloyed particles that benefit from being treated at these higher second temperatures, as it allows for a greater degree of relaxation of the relatively low degree of plastic deformation during compression. In particular, finer powders, for example 200-300 mesh, benefit from a thicker first coating, and the resulting decrease in permeability is generally acceptable for the types of passive members in which these fine powders are typically used.

[0140] As seen in Example 1, dopant inclusion allows for these high heat treatment step temperatures, accompanied by a correspondingly low coercivity, while maintaining an acceptable electrical resistivity and therefore an acceptable core loss.

[0141] The heat treatment may further include an initial pre-oxidation step carried out in ambient air at a temperature of 200-250°C for 1-30 hours, for example, 2-18 hours. This improves the electrical resistivity.

[0142] In particular, the heat treatment step (ii) may include a pre-oxidation step, followed by delubrication at 400-500°C in an inert atmosphere (e.g., nitrogen), and then a hardening and stress relaxation treatment at 600-700°C in 5000-15000 ppm oxygen. This improves the mechanical strength (TRS: Transverse Rupture Strength) without significantly sacrificing magnetic properties such as electrical resistivity, coercivity, and core loss.

[0143] The fifth and sixth embodiments corresponding to the techniques proposed herein relate to an object comprising a compressed ferromagnetic powder composition according to the first embodiment of the techniques proposed herein, or a compressed ferromagnetic powder mixture according to the second embodiment of the techniques proposed herein, and an object obtained by the method according to the fourth embodiment of the techniques proposed herein, respectively.

[0144] The object may also be referred to as a component or part. The object may be selected from the group consisting of soft magnetic components such as sensors, inductors, converters, transformers, motors, and generators.

[0145] Examples In the following embodiments, various ferromagnetic powder compositions containing soft magnetic iron core particles according to a first aspect of the technology proposed herein were manufactured by coating the soft magnetic iron core particles with various first and second coatings, as described in various embodiments of the method according to a third aspect of the technology proposed herein. Subsequently, test parts or test objects were manufactured using the ferromagnetic powder compositions, which were compressed and heat-treated according to various embodiments of the method according to a fourth aspect of the technology proposed herein. Finally, the completed test parts were investigated for relevant properties such as electrical resistivity Res and magnetic permeability μ-max.

[0146] More specifically, the test specimens used in the examples were manufactured in the following steps:

[0147] Step 1: Soft magnetic iron core particles were mixed with an aqueous solution of silicate of general formula (K2O)α(SiO2)β (potassium silicate, manufactured by Sibelco Nordic AB, β / α molar ratio 3.35, solid content 35 wt%) at a concentration of approximately 0.11 wt% (0.165 wt% and 0.275 wt% were also tested) (based on dry material content) for 10 minutes to form a first coating on the core particles. Particles of bismuth and oxygen-containing compounds, specifically 0.08 wt% (0.11 wt% and 0.205 wt% were also tested) of Bi(OH)3 were also present in the aqueous solution unless otherwise specified.

[0148] If the first coating contained nanoparticles, they were Y2O3 particles (nominal 10 nm) at 20 mol% based on the K content, unless otherwise specified.

[0149] The aqueous solutions further contained one or more additional target compounds or additives specified for each sample. After the initial mixing, the core particles were dried with stirring at 60°C for 1 hour, followed by further drying at 120°C without stirring.

[0150] Step 2: The mixture from Step 1 was mixed with silane (Dynasylan 1146, an oligomerge amino-functionalized silane from Evonik Industries AG, 2.0 g) and 1 g of H2O (corresponding to 2 g of silane per 1 kg of core particles coated with the first coating) for 5 minutes unless otherwise specified to form a second coating. The resulting mixture was dried at 50°C for 2 hours to produce a finished ferromagnetic powder composition containing coated soft magnetic iron core particles. (Equivalent to 2 g of silane per 1 kg of core particles with the first coating) was mixed with the mixture for 5 minutes unless otherwise specified to form the second coating.

[0151] Step 3: To facilitate the manufacture of the test specimens, a lubricant (0.4 wt% amide wax unless otherwise specified) was added to the ferromagnetic powder composition, and then the ferromagnetic powder composition was molded and compressed into a test specimen (800 MPa at a die temperature of 100°C). This was then heat-treated as described in detail for each sample to release the stress from the compression and form the completed test specimen.

[0152] Unless otherwise specified, soft magnetic iron core particles conform to 100 mesh dimensions and have a density of 3.32 g / cm³. 3 It was a water atomized annealed iron powder with an apparent density of [value missing].

[0153] The heat treatment was performed in three stages in a preheating furnace. The three stages included a delubrication stage at approximately 300-400°C in which the compressed member was heated toward the hardening stage, a hardening stage at approximately 350-450°C (first time and temperature applied to each sample) in which the coatings hardened to form electrically insulating silicate glass from the first and second coatings, and a relaxation stage at 600-700°C (second time and temperature applied to each sample) in which the stress from compression was released. Unless otherwise specified, the partial pressure of oxygen during the heat treatment was 15,000 ppm (1.5 wt% oxygen in nitrogen).

[0154] The completed test specimen (magnetic square toroid with OD55 / ID45 / H5mm) was subjected to testing, and the following measurements were taken in particular:

[0155] Electrical resistivity (Res) - how well a material resists electric current [μΩm]. Measured using a four-point probe method with a distance of 20 mm between measurement points. Coercivity at 10kA / m*(H c )[A / m] maximum permeability * (μ-max) - The maximum value of the ratio between magnetizations obtained by the material in response to an applied magnetic field [unitless]. Total Core Loss * (1T / 1kHz) - Total core loss [W / kg] of the test member obtained for a given induction and frequency. * For magnetic property measurements, a square toroid was wound with resin-coated copper wire (0.63 mm in diameter) with 100 drive turns and 100 sense turns, and measured using a Brockhaus MPG 200D. References: IEC 60404-4 (DC measurement) and IEC 60404-6 (AC measurement). Furthermore, the following measurements were taken: Density of rectangular toroid (d) - Density of rectangular toroid specimen [g / cm³] 3 ]. Transverse breaking strength [MPa] of a bar with dimensions TRS-30×12×6mm, according to SS-EN ISO 3325:2000. AD - Apparent density [g / cm³] measured as the ratio of the dry mass to the apparent volume of the powder sample, according to ISO standard 3923-1:2018. 3 ]. Whole flow [seconds] according to flow-SS-EN ISO 4490:2018. GS - Green strength (GS: Green strength) [MPa] measured as TRS on test specimens before heat treatment.

[0156] Example 1: Initial experiments with and without nanoparticles and dopants Example 1 tested the effect of adding a dopant to a first coating containing silicate and bismuth and oxygen-containing compound particles. For further investigation, nanoparticles were also added to the first coating. [Table 1A]

[0157] The results in Table 1 illustrate the problems that arise when heat treatment is performed at higher temperatures. While the sample material exhibited an electrical resistivity of 2158 μΩm when heat-treated up to 650°C, heat treatment at a higher temperature of 670°C resulted in an electrical resistivity approximately 86 times lower, at 25 μΩm. Such low electrical resistivity is unacceptable for almost all applications. [Table 1B]

[0158] The results in Table 1B show that the V dopant improved the resistivity of the sample to 5649 μΩm during heat treatment at 650°C, which is approximately 2.6 times that of sample 1-1. More importantly, the resistivity for heat treatment at a higher temperature of 670°C is now 309 μΩm, which is more than 12 times greater than that of sample 1-1, but only about 18 times lower than that of sample 1-2 at the lower temperature of 650°C. Therefore, the addition of the V dopant affected the thermal stability of the coating on the core particles. [Table 1C]

[0159] The results in Table 1C show that the addition of nanoparticles to the first coating increases the electrical resistivity (14841 μΩm for sample 1-3 at 650°C is approximately 6.9 times greater than 2158 μΩm for sample 1-1 at 650°C). When the heat treatment is carried out at a higher temperature of 670°C, the electrical resistivity is 1758 μΩm, which is approximately 8.4 times lower than at lower temperatures. Comparing Tables 1A to 1C, it appears that dopants may have a greater impact on thermal stability, while nanoparticles may have a greater impact on general electrical resistivity levels. [Table 1D]

[0160] The results in Table 1D show that both nanoparticles and dopants provide high electrical resistivity at both lower and higher heat treatment temperatures. Furthermore, the results indicate that dopants retain a higher proportion of electrical resistivity even when using higher temperatures. For example, the electrical resistivity of 9345 μΩm after heat treatment at 670°C with the addition of 10 mol% V dopant is approximately 5.3 times greater than that of samples 1-3 at the same temperature. [Table 1E]

[0161] Table 1E shows the results obtained for higher concentrations of silicate, i.e., thicker first coatings. The results, as in Table 1D, show that the addition of dopant retains a higher proportion of the low-temperature resistivity even when using an even higher temperature of 680°C.

[0162] In summary, these results indicate that the addition of dopants alone, or preferably with nanoparticles, provides better thermal stability and higher electrical resistivity for a given coercivity level and coating density / thickness level.

[0163] Based on these results, it was decided to use a ferromagnetic powder composition in which the first coating contains 20 mol% Y2O3 nanoparticles and has a silicate concentration of 0.11 wt% as a general reference sample for further evaluating the effect of the dopant in the following examples.

[0164] Example 2: The addition of V dopant in the first coating ensures acceptable electrical resistivity even after heat treatment at elevated temperatures. Example 2 further tested the effect of adding a V dopant (in the form of V2O5) to the aqueous silicate in Step 1 when producing the coated soft magnetic iron core particles in Step 2. All samples further contained 20 mol% Y2O3 nanoparticles (nominal 10 nm) and 0.12 wt% bismuth hydroxide (Bi(OH)3) in the first coating, based on the molar weight of K. [Table 2]

[0165] As can be seen from the results, progressively increasing the maximum temperature in the heat treatment step resulted in progressively lower coercivity for the sample. This also applied to the sample to which the V dopant was added. However, these latter samples maintained an acceptable electrical resistivity even at the highest maximum temperature of 700°C, in contrast to the reference sample 1B. Furthermore, the results show that the electrical resistivity increased with increasing dopant content for each heat treatment. Therefore, adding the V dopant, preferably at least 5 mol%, more preferably 10 mol%, and even more preferably 15 mol%, to the solution used to obtain the first coating provides that the component manufactured from the ferromagnetic powder composition can be heat-treated at higher maximum temperatures, such as 680°C and 700°C, thereby obtaining a coercivity value in the range of 132–134 while maintaining an electrical resistivity value in the range of 1889–6214.

[0166] The continuously lower coercivity values ​​obtained for higher amounts of V suggest that less stress is introduced into the coated soft magnetic iron core particles. Although not intended to be constrained by theory, one possible mechanism is the addition of a V2O5 compound to the solution used to obtain the first coating, and consequently the VO4 in the first coating. 3-The inclusion of ions is presumed to result in a more thermally stable first coating, making it less susceptible to crack formation during heat treatment. Improved thermal stability may have several different reasons. While not intended to be theoretically bound, the dopant may i) enhance the electrical resistivity of the bismuth silicate glass. Higher resistivity of the glass may allow for the use of higher relaxation temperatures, which can reduce the viscosity of the formed glass, thus promoting improved coverage of the particle surface. The effect of the dopant may also ii) lower the glass formation temperature, and / or iii) lower the viscosity of the glass, which in turn may improve the distribution of the glass and particle coverage, and / or iv) reduce volume changes between heat treatment or cooling protocols, thereby making crack formation less likely. Cracks expose soft magnetic iron core particles to oxidation, which can not only relatively increase coercivity during heat treatment but also lead to degradation over time with use in high-temperature applications.

[0167] The distribution of the first coating is further enhanced by nanoparticles, which are thought to act, among other things, to prevent crack formation during the drying of the first coating.

[0168] Regardless of the mechanism, the results demonstrate the advantage of including the V dopant in the first coating.

[0169] Example 3: Further experiments using different dopants Further experiments were conducted to determine whether the dopant used in Example 2 could be replaced by other dopants while providing the same or similar improvements to the properties of the test member. The experimental parameters and results are shown in Table 3. [Table 3]

[0170] As can be seen from the table, both the Mo(MoO3) dopant and the Al(Al(OH)3) dopant provide higher electrical resistivity than the reference sample when heat-treated at 450 / 700°C. Therefore, these dopants, like V, allow for heat treatment at higher temperatures to reach lower coercivity values ​​while maintaining an acceptable electrical resistivity value. W provides similar but lower electrical resistivity compared to the reference sample at 450 / 680°C, but retains more of its initial electrical resistivity (6% compared to 5% for the reference sample). It should also be noted that at the two highest temperatures, all samples with dopants had a higher percentage of residual electrical resistivity than the reference sample.

[0171] Example 4: Different amounts of nanoparticles Further experiments were conducted to investigate the results obtained using dopants with different amounts of Y2O3 nanoparticles. The experimental parameters and results are shown in Table 4. [Table 4]

[0172] As can be seen from the table, the dopant is effective even with different amounts of nanoparticles.

[0173] Example 5: Effect of thermal degradation Further experiments were conducted to determine the effect of thermal degradation on the properties of the test specimens. As detailed in Table 5A below, test specimens made from powders produced by heat treatments at 420 / 640°C, 450 / 680°C, and 450 / 700°C were further held at 260°C for 5 days. [Table 5A-1] [Table 5A-2]

[0174] As shown in the table, samples containing the V dopant exhibited better aging characteristics with higher electrical resistivity values.

[0175] Further XRD experiments were performed to investigate the ratio of Fe oxide to Fe on the surface of the powder particles, as shown in Table 5B below. Quantitative analysis of the crystalline phase was performed by Rietveld analysis using HighScore Plus software from Malvern Panalytical. The samples analyzed were flat surfaces of compressed test rods after being subjected to different heat treatments. [Table 5B]

[0176] As shown in the table, samples without dopants had a higher FeOx / Fe ratio than samples with dopants. Therefore, the lower ratio promotes improved aging resistance of heat-treated components due to the improved coverage of the glassy coating. This was true for all dopants tested.

[0177] Example 6: Further experiments using an increased amount of silicate in the first coating. Further experiments were conducted to evaluate the effects of the dopant and the increased amount of silicate in the first coating. The experimental parameters and results are shown in Table 6 below. [Table 6-1] [Table 6-2]

[0178] As can be seen from the table, higher concentrations of silicate generally provide increased resistivity at the expense of lower μ-max.

[0179] Example 7: Further experiments using Al(OH)3 as a dopant Aluminum, for example Al(OH)3, is an interesting dopant because it has a smaller environmental impact and lower health risk than V2O5. Therefore, further experiments were conducted to evaluate the effects of the dopant and the increased amount of silicate in the first coating. For these experiments, silicate solutions with a higher β / α ratio (3.82) were used to compensate for the decrease in the β / α ratio when Al(OH)3 was dissolved using additional KOH. The experimental parameters and results are shown in Table 7 below. [Table 7]

[0180] As can be seen from the table, the Al dopant provided better electrical resistivity than the reference sample at higher temperatures and higher silicate concentrations. At lower silicate concentrations, the Al dopant provided lower but comparable electrical resistivity to the reference sample.

[0181] Example 8: Variation of non-dopant components Further experiments were conducted to evaluate the variation of other components in the first coating in the absence of the dopant. The heat treatment was 450 / 650°C (30 / 30 min). The results are shown in Table 8 below: [Table 8-1] [Table 8-2] [Table 8-3] [Table 8-4]

[0182] As can be seen from the results above, the non-dopant components of ferromagnetic powder compositions can vary widely.

[0183] Example 9: Schematic cross-sectional view of particles of a ferromagnetic powder composition Based on the above examples, Figure 1 shows a very schematic cross-sectional view of a single particle 10 of a ferromagnetic powder composition according to an embodiment of the first aspect of the technology proposed herein. The particle 10 comprises a soft magnetic iron-based core particle 11 covered by a first coating 12 containing a silicate. A second coating 13 is also shown, which contains a metal-organic compound. Particles of the compound, which includes bismuth and oxygen and has an approximate diameter of about 1 μm (one of which is indicated by reference numeral 14), are shown dispersed within the first coating 12. Furthermore, nanoparticles having an approximate diameter of about 10 to 200 nm (one of which is indicated by reference numeral 15) are also shown dispersed within the first coating 12. Finally, a dopant is schematically shown as dissolved in the silicate of the first coating 11, as indicated by reference numeral 16.

[0184] Figure 1 shows the particles before heat treatment, i.e., the particles before compression and heat treatment of the ferromagnetic powder to produce an object according to the method of the fourth aspect of the technique proposed herein. During heat treatment, the particles 14 of the bismuth and oxygen-containing compound are thought to form a uniformly distributed glassy coating (bismuth-silicate glass) together with the silicate having nanoparticles 15 and their dissolved dopant 16 in the first coating 12 and the amino and / or alkyl groups of the metal-organic compound in the second coating 13, which provides electrical resistivity and improved mechanical strength between the individual particles of the compressed and heat-treated ferromagnetic powder composition.

[0185] Figure 1 shows that particles 14 of a compound containing bismuth and oxygen are present in the first coating 12, but it is assumed that the particles 14 of the compound containing bismuth and oxygen may be further dispersed in the second coating 13 or may be separated between the first and second coatings.

[0186] Furthermore, while Figure 1 shows that the first coating 12 and the second coating 13 completely coat the soft magnetic iron core particles 11, one or both of these coatings may alternatively only partially cover the soft magnetic iron core particles 11.

[0187] Example 10: Addition of alloyed soft magnetic powder to a ferromagnetic powder composition Further experiments were conducted to evaluate the effect of adding a further ferromagnetic powder composition, specifically iron-silicon powder (6.8 wt% Si), to a ferromagnetic powder composition containing core particles made of essentially pure iron. Core particles made of essentially pure iron were coated according to the procedure described in Example 1 (0.1375 wt% silicate and 15 mol% V). Alloyed iron-silicon soft magnetic core particles ("FeSi") of the further ferromagnetic powder composition were separately coated with 0.11 wt% silicate (Sample 9-3) or treated with phosphoric acid diluted in acetone (Sample 9-4).

[0188] The reference sample (containing 0.3% amide wax) was compressed at 1100 MPa (die temperature 100°C), and heat treatment was carried out at a maximum of 700°C. The alloyed powder mixture (samples 9-2 to 9-4, containing 0.1% amide wax) was instead compressed at 1600 MPa using die wall lubrication (DWL; die temperature 60°C) and heat treated at a maximum of 740°C. The results are shown in Table 9 below: [Table 9]

[0189] The reference sample (9-1) exhibits excellent density and mechanical strength, but its coercivity and DC loss are higher compared to the alloyed mixture. However, sample 9-2, mixed with 30% FeSi powder, shows a slight reduction in coercivity. However, due to the decrease in density (and permeability μmax), the DC loss is maintained similarly to the reference sample. It has been shown that the DC loss can be significantly reduced by introducing 50% coated FeSi powder; see sample 9-3. Sample 9-4, containing 50% phosphate-coated FeSi powder and a relatively thicker silicate coating (0.165 wt%) on essentially pure iron powder, shows improved total core loss and DC loss compared to the reference sample.

[0190] Example 11: Increase in mechanical strength Further experiments were conducted to evaluate the factors affecting the mechanical strength of objects and components manufactured from ferromagnetic powder compositions. Achieving higher mechanical strength, for example, as measured by transverse fracture strength (TRS), without sacrificing magnetic properties, allows components to be used in more demanding environments, such as in high-speed motors or for heavy-duty robotics. In short, in this embodiment, it was found that by changing the heat treatment parameters, the mechanical and magnetic properties can be tuned to better meet the requirements of different applications.

[0191] Table 10 below lists examples of different heat treatment protocols. The ferromagnetic powder composition was as generally described above and contained 0.11 wt% silicate. The lubricant was amide wax (EBS).

[0192] The standard treatment (Ref.) is carried out in a fixed atmosphere, in which the internal lubricant is carefully removed (approximately 400°C, 20 minutes), immediately followed by a hardening and stress relaxation treatment (615°C, 20 minutes). The fixed atmosphere is typically between 0.5–1.5% oxygen (5000–15000 ppm) in nitrogen. Alternatively, by performing delubrication in an inert atmosphere (e.g., nitrogen), followed by a separate relaxation step at 615°C, 20 minutes in 0.5% oxygen (5000 ppm), the TRS increases (A). However, by introducing a further pre-oxidation step in ambient air between 200–250°C (i.e., below the evaporation temperature of the lubricant), the electrical resistivity is improved (C, E–I). By slightly increasing the oxygen concentration in the final relaxation step, the TRS is further improved without increasing coercivity (D vs. E). Samples F and H provide the highest TRS.

[0193] Pre-oxidation is thought to facilitate the combustion and / or evaporation of the lubricant in a favorable manner. Table 10 also shows that it is advantageous to avoid oxygen in the furnace atmosphere during delubrication, otherwise the coercivity of the ferromagnetic powder composition will increase due to oxidation (D). Furthermore, delubrication during the relaxation process followed by oxidation with 1.5% oxygen (15,000 ppm) should also be avoided (J). [Table 10-1] [Table 10-2]

[0194] Feasible modifications of the techniques proposed herein The technologies proposed herein are not limited to the embodiments described above and shown in the drawings, which are primarily illustrative and for illustrative purposes. This patent application is intended to cover all modifications and variations of the preferred embodiments described herein. Accordingly, the present invention is defined by the wording of the appended claims and equivalents.

[0195] Throughout this specification and the appended claims, unless otherwise required by context, the word “comprise,” and variations such as “comprises” or “comprising,” are understood to mean that they include the integers or steps, or groups of integers or steps, described, but not any other integers or steps, or groups of integers or steps.

Claims

1. A ferromagnetic powder composition, (i) Soft magnetic iron core particles, (ii) A first coating that at least partially covers and is in direct contact with the surface of the core particles, Includes, The first coating is a. General formula (K 2 O)α(SiO 2 ) It is a silicate of β, and α is K 2 It is the number of moles of O, and β is SiO 2 The number of moles is such that the silicate has a β / α molar ratio in the range of 0.5 to 4.

1. i. The silicate is present in an amount of 0.02% to 1.0% by weight, calculated based on the total weight of the ferromagnetic powder composition, b. Optionally, D measured according to ISO (International Organization for Standardization) 13320-1. 50 Particles of a compound containing bismuth and oxygen, which are in the range of 0.1 μm to 10 μm, c. A dopant dissolved as an oxoanion or hydroxyanion in the silicate (a), A ferromagnetic powder composition containing [the specified element].

2. The first coating is further measured according to ISO 13320-1. 50 The surface has a surface area of ​​10–200 nm, or alternatively, a specific surface area (SSA) of 6–120 m² as measured according to ISO 9277:2022. 2 The ferromagnetic powder composition according to claim 1, comprising nanoparticles having / g.

3. The nanoparticles are Y 2 O 3 nanoparticles, ZrO 2 nanoparticles, ZnO nanoparticles, Mg(OH) 2 nanoparticles, MgO nanoparticles, CaCO 3 nanoparticles, Al 2 O 3 nanoparticles, SiO 2 nanoparticles, and TiO 2 nanoparticles, the nanoparticles preferably comprise or consist of Y 2 O 3 nanoparticles, The ferromagnetic powder composition according to claim 2.

4. The ferromagnetic powder composition according to claim 2 or 3, wherein the content of nanoparticles in the first coating is 1 to 30 mol%, preferably 1 to 20 mol%, based on the molar content of K (potassium) in the first coating.

5. The aforementioned nanoparticles are Y 2 O 3 Contains nanoparticles or Y 2 O 3 The ferromagnetic powder composition according to any one of claims 2 to 4, comprising nanoparticles, wherein the content of nanoparticles in the first coating is 10 to 20 mol% based on the molar content of K (potassium) in the first coating.

6. The ferromagnetic powder composition according to any of the above claims, wherein the dopant comprises at least one element from Group 5, for example V (vanadium) or Nb (niobium), or at least one element from Group 6, for example Cr (chromium), W (tungsten), or Mo (molybdenum), or comprises Al (aluminum) or P (phosphorus).

7. - The dopant contains V, and the dopant content in the first coating is 1 to 30 mol%, preferably 5 to 20 mol%, and more preferably 5 to 15 mol%, based on the molar content of K (potassium) in the first coating. - The dopant contains Nb, and the dopant content in the first coating is 1 to 30 mol%, preferably 5 to 20 mol%, and more preferably 5 to 15 mol%, based on the molar content of K in the first coating. - The dopant contains Cr, and the dopant content in the first coating is 1 to 30 mol%, preferably 5 to 20 mol%, and more preferably 5 to 15 mol%, based on the molar content of K in the first coating. - The dopant contains Mo, and the dopant content in the first coating is 1 to 30 mol%, preferably 5 to 20 mol%, and more preferably 5 to 15 mol%, based on the molar content of K in the first coating. - The dopant contains W, and the dopant content in the first coating is 1 to 30 mol%, preferably 5 to 20 mol%, and more preferably 5 to 15 mol%, based on the molar content of K in the first coating. - The dopant contains Al, and the dopant content in the first coating is 0.5 to 5 mol%, preferably 1 to 3 mol%, more preferably 1.71 to 2.58 mol%, and / or, based on the molar content of K in the first coating. - The ferromagnetic powder composition according to any one of the claims, wherein the dopant contains P, and the dopant content in the first coating is 1 to 30 mol%, preferably 5 to 20 mol%, more preferably 5 to 15 mol%, based on the molar content of K in the first coating.

8. The ferromagnetic powder composition according to any one of the claims, wherein the dopant comprises V, and the dopant content in the first coating is 1 to 30 mol%, preferably 5 to 20 mol%, and more preferably 10 to 15 mol%, based on the molar content of K in the first coating.

9. A ferromagnetic powder composition according to any of the above claims, wherein the β / α molar ratio is in the range of 2.0 to 4.

1.

10. The first coating comprises particles of a compound containing bismuth and oxygen, the particles being measured according to ISO 13320-1. 50 A ferromagnetic powder composition according to any of the above claims, wherein the particle size is in the range of 0.1 to 10 μm.

11. The ferromagnetic powder composition according to any one of the above claims, wherein the oxoanion or hydroxyanion of the dopant is a monoanion.

12. moreover, (iii) A second coating comprising at least partially covering the surface of the core particles and / or the first coating, the second coating is a. general formula R 1 [(R 1 ) x (R 2 ) y (M)] n O n-1 R 1 (I) or ( 2 [*()) 2(n+1) ] (n+1) . (n) ( 2 (=) It comprises at least one metal-organic compound having, Here, M is selected from the group consisting of Si, Ti, Al, and Zr, O is oxygen, and R 1 R is a hydrolyzable group, 2 is an organic part, and has at least one R 2 It contains at least one nitrogen-containing group, preferably an amino group, n is the number of repeating units which is an integer from 1 to 20, x is 0 or 1, y is 1 or 2, and x + y is 2. The ferromagnetic powder composition according to any of the claims, wherein the content of at least one of the metal-organic compounds is 0.05 to 0.40% by weight, preferably 0.10 to 0.30% by weight, based on the total weight of the ferromagnetic powder composition.

13. A ferromagnetic powder mixture, wherein the ferromagnetic powder mixture is - The ferromagnetic powder composition according to any of the above claims, - Further ferromagnetic powder compositions, Includes, The further ferromagnetic powder composition comprises soft magnetic iron core particles that are different from the soft magnetic iron core particles of the ferromagnetic powder composition, Preferably, the ferromagnetic powder mixture comprises or consists of an iron alloy having a higher electrical resistivity and / or hardness than the soft magnetic iron core particles of the further ferromagnetic powder composition.

14. The ferromagnetic powder mixture according to claim 13, wherein the soft magnetic iron core particles of the further ferromagnetic powder composition include or consist of an iron alloy selected from the group consisting of FeSi, FeAl, FeSiAl, FeNi, FeCo, and FeNiCo, or a combination or mixture of such alloys.

15. The ferromagnetic powder mixture according to claim 14, wherein the iron alloy is preferably selected from the group consisting of FeSi containing 3-6.8% by weight of Si, and preferably FeSiAl containing 9% by weight of Si and 6% by weight of Al, or FeSiAl containing 3.5% by weight of Si and 3% by weight of Al.

16. The ferromagnetic powder mixture according to any one of claims 13 to 15, wherein the content of the further ferromagnetic powder composition is, based on the weight of the ferromagnetic powder mixture, up to 90% by weight, for example 30 to 60% by weight or 10 to 50% by weight, preferably 20 to 40% by weight, for example 20 to 30% by weight, or alternatively 40 to 60% by weight, for example 45 to 55% by weight.

17. A method for producing a ferromagnetic powder composition, (i) The step of providing soft magnetic iron core particles, (ii) A step of bringing the soft magnetic iron core particles into contact with the first aqueous solution, The first aqueous solution is a. General formula (K 2 O)α(SiO 2 ) It is a silicate of β, and α is K 2 It is the number of moles of O, and β is SiO 2 The number of moles is such that the silicate has a β / α molar ratio in the range of 0.5 to 4.

1. i. The silicate is present in an amount of 0.02% to 1.0% by weight, calculated based on the total weight of the ferromagnetic powder composition, b. Optionally, D measured according to ISO 13320-1 50 Particles of a compound containing bismuth and oxygen, which are in the range of 0.1 μm to 10 μm, c. A dopant dissolved as an oxoanion or hydroxyanion in the silicate (a), d. Optionally, D measured according to ISO 13320-1 50 Nanoparticles having a size of 10 nm to 200 nm, or alternatively, 6 to 120 nm as measured according to ISO 9277:2022. 2 Nanoparticles having a specific surface area (SSA) of / g, Step, an aqueous solution containing, A method for producing a ferromagnetic powder composition containing [a specific substance].

18. moreover, (iii) A step of drying the soft magnetic iron core particles, and / or (iv) The soft magnetic iron core particles are given the general formula R 1 [(R 1 ) x (R 2 ) y (M)] n O n-1 R 1 (I) or ( 2 [*()) 2(n+1) ] (n+1) . (n) ( 2 (=) A step of contacting with at least one organometallic compound having, Here, M is selected from the group consisting of Si, Ti, Al, and Zr, O is oxygen, and R 1 R is a hydrolyzable group, 2 is an organic part, and has at least one R 2 It contains at least one nitrogen-containing group, preferably an amino group, n is the number of repeating units which is an integer from 1 to 20, x is 0 or 1, y is 1 or 2, and x + y is 2. Step and / or, based on the total weight of the ferromagnetic powder composition, the content of at least the metal-organic compound is 0.05 to 0.40% by weight, preferably 0.10 to 0.30% by weight. (v) A step of mixing the soft magnetic iron core particles with a lubricant, preferably a particulate lubricant. The method according to claim 17, comprising one or more steps.

19. (i) A step of obtaining a compressed member by compressing a ferromagnetic powder composition according to any one of claims 1 to 12 or a ferromagnetic powder mixture according to any one of claims 13 to 16 in a die at a compression pressure in the range of 300 to 2000 MPa, preferably 400 to 1200 MPa, (ii) The compression member is subjected to a non-reducing atmosphere, preferably 0 to 22% by weight, more preferably 0.5 to 2% by weight of oxygen (O 2 The steps include obtaining an object by heat treatment in an atmosphere containing ) at a temperature in the range of 300 to 800°C, preferably 400 to 750°C, more preferably 600 to 700°C, A method for producing an object from a ferromagnetic powder composition according to any one of claims 1 to 12 or a ferromagnetic powder mixture according to any one of claims 13 to 16, comprising the above.

20. The method according to claim 19, wherein step (ii) includes heat-treating the compressed body at a temperature of 670 to 700°C, preferably 680 to 700°C.

21. An object comprising a compressed ferromagnetic powder composition according to any one of claims 1 to 12 or a compressed ferromagnetic powder mixture according to any one of claims 13 to 16.